Resistance to OsHV-1 Infection in Crassostrea gigas Larvae - Dégremont, Lionel; Morga, Benjamin; Trancart, Suzanne; Pépin, Jean-François (Frontiers in Marine Science, 2016)
The ostreid herpesvirus (OsHV-1) is one of the major diseases that affect the Pacific oyster Crassostrea gigas. Selective breeding programs were recently shown to improve resistance easily to OsHV-1 infections in spat, juvenile and adult oysters. Nevertheless, this resistance has never been investigated in larvae, whereas this developmental stage has crucial importance for the production of commercial hatcheries, as well as explaining the abundance of spatfall. A first trial tested several viral suspensions at several concentrations using contaminated water with OsHV-1 in four-day-old and ten-day-old larvae that were produced from an unselected broodstock. In follow up on the results, one viral suspension at a final concentration of 10+6 OsHV-1 DNA copies per L was used to assess resistance to OsHV-1 infection in C. gigas larvae that were produced from selected and unselected broodstock. A second trial evaluated OsHV-1 resistance in larvae from both broodstocks in trials 2a, 2b and 2c with 4, 10 and 16-day-old larvae for 7 days, which corresponded to post D larvae, umbo larvae and eyed larvae, respectively. The mortality of unchallenged larvae for both stocks were low (<15%) at day 7 in trials 2a and 2b, whereas it ranged from 48 to 56% in trial 2c. More interestingly, selected larvae had significantly lower mortality than unselected larvae when exposed to OsHV-1 in all of the trials. Thus, the mortality was 11% and 49% for the selected larvae at day 7 post-exposure in trials 2a and 2c, respectively, in comparison with 84% and 97% for the unselected larvae. Although this difference in mortality was observed at day 5 in trial 2b, it was reduced at day 7, to 86% and 98% for the selected and unselected larvae, respectively. For the first time in the literature, the difference in mortality or the delayed onset of mortality between selected and unselected larvae have indicated a genetic resistance to OsHV-1 infection at the larval stage. Such finding should facilitate the selective breeding programs focusing on resistance to OsHV-1 infection by reducing the span of the genetic evaluation, and thus decreasing its cost